Nonaqueous electrolyte solution, electrochemical device, and electronic device

By using a non-aqueous electrolyte with specific contents of dimethyl carbonate or ethyl acetate and dinitrile substances in an electrochemical device, the battery cycle life and self-discharge performance problems caused by chain carbonate electrolyte are solved, and a longer cycle life and lower self-discharge phenomenon are achieved.

CN119786743APending Publication Date: 2025-04-08NINGDE AMPEREX TECHNOLOGY LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510005835.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In existing electrochemical devices, chain carbonate electrolytes are prone to dehydrogenation to produce hydrogen ions, resulting in the destruction of the structure of the positive electrode material and corrosion of the negative electrode current collector, which in turn affects the cycle life and self-discharge performance of the battery.

Method used

A non-aqueous electrolyte is used, including specific contents of dimethyl carbonate or ethyl acetate and dinitrile substances. By regulating its mass proportion, it can improve the electrolyte dissolution ability and reduce the electrolyte viscosity, and inhibit side reactions and corrosion of the negative electrode current collector.

Benefits of technology

The non-aqueous electrolyte can significantly improve the cycle life of the battery and reduce self-discharge phenomenon, while avoiding corrosion of the positive electrode material and the negative electrode current collector.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005227192250000031
    Figure BDA0005227192250000031
  • Figure BDA0005227192250000032
    Figure BDA0005227192250000032
  • Figure BDA0005227192250000041
    Figure BDA0005227192250000041
Patent Text Reader

Abstract

The invention discloses a non-aqueous electrolyte, an electrochemical device and an electronic device. The non-aqueous electrolyte solution includes a first substance and a second substance. The first substance includes at least one of dimethyl carbonate or ethyl acetate. Based on the total mass of the non-aqueous electrolyte, the mass ratio of the first substance is M1%, and M1 is more than or equal to 50 and less than or equal to 70; the second substance comprises at least one of butanedinitrile, glutaronitrile or adiponitrile, the mass ratio of the second substance is M2% based on the total mass of the non-aqueous electrolyte, and M2 is larger than or equal to 0.01 and smaller than or equal to 3. The electrochemical device provided by the invention has relatively excellent discharge performance, especially relatively excellent cycle performance and relatively low self-discharge level.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy storage technology, and in particular to non-aqueous electrolytes, electrochemical devices and electronic devices. Background Art

[0002] Electrochemical devices are playing an increasingly important role as power sources for electronic products. As one of the important components of electrochemical devices, the physical and chemical properties of electrolytes are directly related to the discharge performance of electrochemical devices. Chain carbonates are widely used as non-aqueous solvents in electrolytes due to their good solubility and ultra-low viscosity. However, chain carbonates are easily dehydrogenated to produce hydrogen ions, which destroy the structure of the positive electrode material and corrode the negative electrode current collector. Therefore, improving the electrochemical properties of chain carbonate electrolytes has become a top priority. Summary of the invention

[0003] The embodiments of the present application provide a non-aqueous electrolyte, an electrochemical device, and an electronic device, which improve the cycle life while also improving the self-discharge phenomenon of the battery.

[0004] In a first aspect, an embodiment of the present application provides a non-aqueous electrolyte, the non-aqueous electrolyte comprising a first substance and a second substance; the first substance comprises at least one of dimethyl carbonate or ethyl acetate, and based on the total mass of the non-aqueous electrolyte, the mass proportion of the first substance is M1%, 50≤M1≤70. The second substance comprises at least one of succinonitrile, glutaronitrile or adiponitrile; based on the total mass of the non-aqueous electrolyte, the mass proportion of the second substance is M2%, 0.01≤M2≤3.

[0005] The non-aqueous electrolyte based on the embodiment of the present application includes a specific content of the first substance dimethyl carbonate or ethyl acetate and the second substance dinitrile, which has a strong electrolyte dissolving ability and a low electrolyte viscosity, and can improve the cycle life of the battery. On this basis, the inventor found that dinitrile substances can be adsorbed on the surface of the positive electrode, reducing the α-H effect of alkaline substances on the surface of the positive electrode material on dimethyl carbonate or ethyl acetate in the electrolyte, and inhibiting the occurrence of side reactions; at the same time, it can also react with the negative electrode current collector to generate insoluble substances, forming a protective layer on the surface of the current collector, reducing the self-discharge caused by the corrosion of the negative electrode current collector, thereby synergizing with the chain carbonate to improve the cycle life of the electrochemical device and taking into account the improvement of the self-discharge phenomenon.

[0006] In some embodiments, the non-aqueous electrolyte satisfies at least one of the following conditions: (1) 55≤M1≤65; (2) 0.1≤M2≤2. Based on the above embodiments, the present application can further improve the cycle life of the electrochemical device while improving the self-discharge phenomenon by adjusting the mass ratio of the first substance or the second substance in the electrolyte to meet the above range.

[0007] In some embodiments, the non-aqueous electrolyte includes ethylene carbonate, and based on the total mass of the non-aqueous electrolyte, the mass proportion of ethylene carbonate is M3%, 5≤M3≤30. Based on the above embodiments, the present application controls the content of ethylene carbonate, on the one hand, to increase the dissociation of lithium salts and improve the conductivity of the electrolyte, and on the other hand, ethylene carbonate can be reduced to a polymer protective film at the negative electrode to reduce the interface impedance, thereby being able to cooperate with the dinitrile compound to further improve the cycle life of the electrochemical device while taking into account the improvement of the self-discharge phenomenon.

[0008] In some embodiments, the non-aqueous electrolyte includes a third substance, and the third substance includes at least one of lithium tetrafluoroborate, lithium bisoxalate borate, lithium difluorooxalate borate, sodium tetrafluoroborate, sodium bis(oxalate) borate, sodium difluorooxalate borate, potassium tetrafluoroborate, potassium bisoxalate borate, potassium difluorooxalate borate, cesium tetrafluoroborate, cesium bisoxalate borate or cesium difluorooxalate borate; based on the total mass of the non-aqueous electrolyte, the mass proportion of the third substance is M4%, 0.001≤M4≤0.5. Based on the above embodiment, the non-aqueous electrolyte of the present application further includes a third substance, a boron-containing lithium salt, and the electron-deficient boron element can combine with the lattice oxygen on the surface of the positive electrode material to form a protective layer, weakening the oxidation effect of the lattice oxygen on the α-H of dimethyl carbonate or ethyl acetate, inhibiting the occurrence of side reactions, and reducing the oxidation of the solvent at the positive electrode, which can further improve the cycle life of the electrochemical device while taking into account the improvement of the self-discharge phenomenon.

[0009] In some embodiments, the non-aqueous electrolyte comprises a compound of formula I:

[0010]

[0011] Among them, R 11 , R 12 , R 13 and R 14 are independently selected from a hydrogen atom, a fluorine atom, a C1 to C3 alkyl group or a fluorine-substituted C1 to C3 alkyl group, and R 11 , R 12 , R 13 or R 14 At least one of them is a fluorine atom; based on the total mass of the non-aqueous electrolyte, the mass proportion of the compound of formula I is a%, 0.01≤a≤1. Based on the above embodiments, the non-aqueous electrolyte of the present application further includes a compound of formula I, which can form a protective film on the surface of the negative electrode during the cycle, inhibit the reduction reaction of the components in the electrolyte on the surface of the negative electrode, reduce the increase of the negative electrode impedance, and inhibit the volume expansion of the pole piece under high temperature conditions, thereby improving the cycle life and self-discharge performance of the electrochemical device while taking into account the improvement of the high-temperature storage expansion phenomenon.

[0012] In some embodiments, the compound of formula I above includes at least one of the following compounds:

[0013]

[0014]

[0015] Based on the above embodiments, the present application can more efficiently generate a protective film on the surface of the negative electrode by selecting the above-mentioned compound of formula I, inhibit the reduction reaction of the components in the electrolyte on the surface of the negative electrode, reduce the increase in the negative electrode impedance, and inhibit the volume expansion of the electrode under high temperature conditions, thereby further improving the cycle life and self-discharge performance of the electrochemical device while also improving the high-temperature storage expansion phenomenon.

[0016] In some embodiments, the non-aqueous electrolyte comprises a compound of formula II:

[0017]

[0018] Among them, R 21 , R 22 , R 23 , R 24 At least one independently selected from a hydrogen atom, a fluorine atom, an unsubstituted or fluorine-substituted methyl, ethyl, n-propyl, isopropyl, vinyl or ethynyl group;

[0019] Based on the total mass of the non-aqueous electrolyte, the mass proportion of the compound of formula II is b%, 0.01≤b≤0.3. Based on the above embodiment, the present application introduces the compound of formula II to reduce and form a protective film containing components such as Li2SO4 and Li2S on the surface of the negative electrode. The protective film has Li + The characteristics of strong conduction ability and low impedance can improve the cycle life and self-discharge performance of electrochemical devices while also improving the high-temperature storage expansion phenomenon.

[0020] In some embodiments, the compound of formula II comprises at least one of the following compounds:

[0021] Based on the above embodiments, the present application can further improve the cycle life and self-discharge performance of the electrochemical device while improving the high-temperature storage expansion phenomenon by selecting the above-mentioned compound of formula II.

[0022] In some embodiments, the non-aqueous electrolyte comprises a compound of formula III:

[0023]

[0024] Among them, R 31 , R 32 , R 33, R 34 , R 35 and R 36 Independently selected from hydrogen atoms, fluorine atoms, C1 to C3 alkyl groups or fluorine-substituted C1 to C3 alkyl groups; based on the total mass of the non-aqueous electrolyte, the mass proportion of the compound of formula III is c%, 0.1≤c≤3. Based on the above embodiment, the present application can form an interface protection film containing Li2SO3 on the surface of the positive electrode by introducing the compound of formula III. The interface protection film can reduce the occurrence of side reactions on the one hand, and has good Li + The conduction capability can improve the cycle life and self-discharge performance of the electrochemical device while also improving the high-temperature storage expansion phenomenon.

[0025] In some embodiments, the compound of formula III above includes at least one of the following compounds:

[0026]

[0027] Based on the above embodiments, the present application can further improve the cycle life and self-discharge performance of the electrochemical device while improving the high-temperature storage expansion phenomenon by selecting the above-mentioned compound of formula III.

[0028] In the second aspect, the embodiment of the present application provides an electrochemical device, including the above-mentioned non-aqueous electrolyte of the electrode assembly; the electrode assembly includes a positive electrode, a separator and a negative electrode stacked and wound in sequence; the positive electrode includes a positive electrode current collector and a positive electrode active material layer arranged on at least one surface of the above-mentioned positive electrode current collector, and the positive electrode active material layer includes nickel; based on the total mass of the positive electrode active material layer, the mass proportion of the nickel element is m%, 30≤m≤56. Based on the above embodiment, the positive electrode active material layer of the electrochemical device of the present application includes nickel, and its material surface has alkaline substances, which makes it easier to remove α-H in the electrolyte components. On this basis, the above-mentioned non-aqueous electrolyte is used in combination, and the dinitrile substances in the electrolyte can be adsorbed on the surface of the positive electrode, reducing the effect of the alkaline substances on the surface of the positive electrode material on the α-H of dimethyl carbonate or ethyl acetate in the electrolyte, inhibiting the occurrence of side reactions, and improving the cycle life and self-discharge performance of the electrochemical device while taking into account the improvement of the high-temperature storage expansion phenomenon.

[0029] In some embodiments, the positive electrode active material in the positive electrode active material layer includes Li x Ni y M 1-y O 2-z A z, 0.9≤x≤1.2, 0.5≤y≤0.85, 0≤z≤0.2. Among them, the M element is selected from at least one of aluminum, magnesium, manganese, cobalt, iron, chromium, vanadium, titanium, copper, calcium, zinc, zirconium, niobium, molybdenum, strontium, antimony, tungsten or bismuth. The A element is selected from at least one of fluorine, phosphorus, sulfur, boron, silicon or chlorine. Based on the above embodiments, the positive electrode active material layer of the electrochemical device of the present application includes the above active material, which can better cooperate with the electrolyte, thereby improving the cycle life and self-discharge performance of the electrochemical device while taking into account the improvement of high-temperature storage expansion phenomenon.

[0030] In some embodiments, the outermost circle of the electrode assembly has a tail section; the electrode assembly includes adhesive tape, and the adhesive tape is bonded to the tail section; the width of the adhesive tape is W mm, 10≤W≤25. Based on the above embodiments, the electrochemical device of the present application can alleviate the problem of the adhesive tape falling off due to the similar molecular polarity of dimethyl carbonate or ethyl acetate in the electrolyte and the adhesive on the adhesive tape being soluble, thereby improving the cycle life and self-discharge performance of the electrochemical device while taking into account the improvement of the high-temperature storage expansion phenomenon.

[0031] In some embodiments, the adhesive tape includes a substrate and an adhesive layer; the thickness of the substrate is Tμm, 10≤T≤50. Based on the above embodiments, the present application can reduce the problem of swelling and shedding of the adhesive tape substrate caused by electrolyte seepage by limiting the thickness of the substrate within the above range, thereby improving the cycle life and self-discharge performance of the electrochemical device while also improving the high-temperature storage expansion phenomenon.

[0032] In a third aspect, an embodiment of the present application provides an electronic device, which includes the above-mentioned electrochemical device. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.

[0034] A first aspect of an embodiment of the present application provides an electrochemical device, including a non-aqueous electrolyte and an electrode assembly, wherein the electrode assembly includes a positive electrode, a negative electrode, and a separator that are sequentially stacked and wound.

[0035] Non-aqueous electrolyte

[0036] The nonaqueous electrolyte used in the electrochemical device of the present application includes an electrolyte and a solvent that dissolves the electrolyte.

[0037] In some embodiments, the non-aqueous electrolyte includes a first substance and a second substance. The first substance includes at least one of dimethyl carbonate or ethyl acetate. Based on the total mass of the non-aqueous electrolyte, the mass proportion of the first substance is M1%, 50≤M1≤70, preferably 55≤M1≤65. For example, the mass proportion of the first substance in the non-aqueous electrolyte can be 50, 51, 55, 58, 62, 65, 69, 70 or a value within the range of any two of these values. The second substance includes at least one of succinonitrile, glutaronitrile or adiponitrile. Based on the total mass of the non-aqueous electrolyte, the mass proportion of the second substance is M2%, 0.01≤M2≤3, preferably 0.1≤M2≤2. For example, the mass proportion of the second substance in the non-aqueous electrolyte can be 0.01, 0.1, 0.16, 0.50, 0.70, 1.00, 1.27, 1.81, 2, 2.45, 2.71, 3 or a value within the range of any two of these values. The non-aqueous electrolyte includes a specific amount of dimethyl carbonate or ethyl acetate and dinitrile substances, which can improve the cycle life of the electrochemical device while also improving the self-discharge phenomenon.

[0038] In some embodiments, the non-aqueous electrolyte includes ethylene carbonate, and the mass percentage of ethylene carbonate is M3% based on the total mass of the non-aqueous electrolyte, 5≤M3≤30. For example, the mass percentage of ethylene carbonate in the non-aqueous electrolyte can be 5, 9, 11, 17, 18, 25, 27, 30 or a value in the range of any two of these values. The non-aqueous electrolyte further includes a specific content of ethylene carbonate, which can further improve the cycle life of the electrochemical device while also improving the self-discharge phenomenon.

[0039] In some embodiments, the non-aqueous electrolyte includes a third substance, and the third substance includes at least one of lithium tetrafluoroborate, lithium bisoxalate borate, lithium difluorooxalate borate, sodium tetrafluoroborate, sodium bis(oxalate) borate, sodium difluorooxalate borate, potassium tetrafluoroborate, potassium bisoxalate borate, potassium difluorooxalate borate, cesium tetrafluoroborate, cesium bisoxalate borate or cesium difluorooxalate borate. Based on the total mass of the non-aqueous electrolyte, the mass proportion of the third substance is M4%, 0.001≤M4≤0.5. For example, the mass proportion of the third substance in the non-aqueous electrolyte can be 0.001, 0.067, 0.130, 0.210, 0.280, 0.407, 0.463, 0.5 or a value within the range of any two of these values. The non-aqueous electrolyte further includes a specific content of a boron-containing lithium salt, which can further improve the cycle life of the electrochemical device while taking into account the improvement of the self-discharge phenomenon.

[0040] In some embodiments, the non-aqueous electrolyte comprises a compound of formula I:

[0041]

[0042] Among them, R 11 , R 12 , R 13 and R 14 are independently selected from a hydrogen atom, a fluorine atom, a C1 to C3 alkyl group or a fluorine-substituted C1 to C3 alkyl group, and R 11 , R 12 , R 13 or R 14 At least one of them is a fluorine atom. Based on the total mass of the non-aqueous electrolyte, the mass proportion of the compound of formula I is a%, 0.01≤a≤1. For example, the mass proportion of the compound of formula I in the non-aqueous electrolyte can be 0.01, 0.06, 0.27, 0.47, 0.66, 0.88, 1 or a value in the range composed of any two of these values. The non-aqueous electrolyte further includes a specific content of the compound of formula I, which can form a protective film on the surface of the negative electrode during the cycle, and can further improve the cycle life and self-discharge performance of the electrochemical device while taking into account the improvement of the high-temperature storage expansion phenomenon.

[0043] In some embodiments, the compound of formula I comprises at least one of the following compounds:

[0044]

[0045]

[0046] By selecting the compound of formula I, a protective film can be more efficiently generated on the negative electrode surface, thereby further improving the cycle life and self-discharge performance of the electrochemical device while also improving the high-temperature storage expansion phenomenon.

[0047] In some embodiments, the non-aqueous electrolyte comprises a compound of formula II:

[0048]

[0049] Among them, R 21 , R 22 , R 23 , R 24Independently selected from at least one of a hydrogen atom, a fluorine atom, a methyl group, an ethyl group, an n-propyl group, an isopropyl group, a vinyl group or an ethynyl group which is unsubstituted or substituted with fluorine. Based on the total mass of the non-aqueous electrolyte, the mass proportion of the compound of formula II is b%, and 0.01≤b≤0.3. For example, the mass proportion of the compound of formula II in the non-aqueous electrolyte can be 0.01, 0.04, 0.10, 0.11, 0.17, 0.22, 0.3 or a value within the range composed of any two of these values. The non-aqueous electrolyte further includes a specific content of the compound of formula II, which can further improve the cycle life and self-discharge performance of the electrochemical device while taking into account the improvement of the high-temperature storage expansion phenomenon.

[0050] In some embodiments, the compound of formula II includes at least one of the following compounds:

[0051] By selecting the compound of formula II, the high-temperature storage expansion phenomenon can be improved while further improving the cycle life and self-discharge performance of the electrochemical device.

[0052] In some embodiments, the non-aqueous electrolyte comprises a compound of formula III:

[0053]

[0054] Among them, R 31 , R 32 , R 33 , R 34 , R 35 and R 36 Independently selected from hydrogen atoms, fluorine atoms, C1 to C3 alkyl groups or fluorine-substituted C1 to C3 alkyl groups; based on the total mass of the non-aqueous electrolyte, the mass proportion of the compound of formula III is c%, 0.1≤c≤3. For example, the mass proportion of the compound of formula III in the non-aqueous electrolyte can be 0.1, 0.2, 0.6, 1.3, 1.9, 2.3, 2.5, 3 or a value in the range of any two of these values. The non-aqueous electrolyte further includes a specific content of the compound of formula III, which can further improve the cycle life and self-discharge performance of the electrochemical device while taking into account the improvement of the high-temperature storage expansion phenomenon.

[0055] In some embodiments, the compound of formula III includes at least one of the following compounds:

[0056]

[0057] By selecting the compound of formula III, the high-temperature storage expansion phenomenon can be improved while further improving the cycle life and self-discharge performance of the electrochemical device.

[0058] In some embodiments, the lithium salt in the non-aqueous electrolyte of the present application may also include, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiPO2F2), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and lithium bis(fluorosulfonyl)imide (LiFSI). Based on the mass of the non-aqueous electrolyte, the mass proportion of the lithium salt may be 8% to 13%, for example, the mass proportion of the lithium salt may be 8%, 9%, 10%, 11%, 12.5%, 13%, or a range consisting of any two of these values.

[0059] The present application has no particular restrictions on the types of other non-aqueous solvents, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of other carbonate compounds, other carboxylate compounds, ether compounds or other organic solvents. For example, other carbonate compounds may include but are not limited to at least one of diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate or methyl ethyl carbonate, propylene carbonate, butylene carbonate or vinyl ethylene carbonate. For example, other carboxylate compounds may include but are not limited to at least one of methyl formate, methyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone or caprolactone. For example, ether compounds may include but are not limited to at least one of ethylene glycol dimethyl ether, dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. For example, other organic solvents may include, but are not limited to, at least one of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, or trioctyl phosphate.

[0060] positive electrode

[0061] The positive electrode includes a positive electrode collector and a positive electrode active material layer disposed on at least one surface of the positive electrode collector.

[0062] In some embodiments, the positive electrode active material layer includes nickel. Based on the total mass of the positive electrode active material layer, the mass percentage of the nickel element is m%, 30≤m≤56. For example, the mass percentage of the nickel element in the positive electrode active material layer can be 30, 37, 41, 46, 48, 53, 56 or a value in the range of any two of these values. The positive electrode active material layer includes nickel, and the use of the above-mentioned non-aqueous electrolyte system can improve the cycle life and self-discharge performance of the electrochemical device while taking into account the improvement of high-temperature storage expansion phenomenon.

[0063] In some embodiments, the positive electrode active material in the positive electrode active material layer includes Li x Ni y M 1-y O 2-z A z , 0.9≤x≤1.2, 0.5≤y≤0.85, 0≤z≤0.2. For example, the value of x can be 0.9, 1.0, 1.1, 1.2 or a value in the range of any two of these values. For example, the value of y can be 0.5, 0.6, 0.7, 0.8, 0.85 or a value in the range of any two of these values. For example, the value of z can be 0, 0.1, 0.2 or a value in the range of any two of these values. Among them, the M element is selected from at least one of aluminum, magnesium, manganese, cobalt, iron, chromium, vanadium, titanium, copper, calcium, zinc, zirconium, niobium, molybdenum, strontium, antimony, tungsten or bismuth. The A element is selected from at least one of fluorine, phosphorus, sulfur, boron, silicon or chlorine. The positive electrode active material layer includes the above active material, which can better cooperate with the electrolyte, improve the cycle life and self-discharge performance of the electrochemical device, and improve the high-temperature storage expansion phenomenon.

[0064] In some embodiments, the positive electrode material layer includes a positive electrode conductive material. There is no limitation on the type of positive electrode conductive material, and any known conductive material can be used. Examples of positive electrode conductive materials may include, but are not limited to, carbon black such as acetylene black and Super-P; amorphous carbon such as needle coke; carbon nanotubes; graphene, etc. The above positive electrode conductive materials may be used alone or in any combination.

[0065] In some of the embodiments, the positive electrode material layer includes a positive electrode binder; the type of the positive electrode binder is not particularly limited, and in the case of a coating method, any material that can be dissolved or dispersed in a liquid medium used in electrode manufacturing can be used. Examples of positive electrode binders may include, but are not limited to, one or more of the following: resin polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, nitrocellulose, etc.; rubber polymers such as styrene-butadiene rubber, nitrile rubber, fluororubber, isoprene rubber, polybutadiene rubber, ethylene-propylene rubber, etc.; thermoplastic elastomer polymers such as styrene-butadiene-styrene block copolymers or their hydrides, ethylene-propylene-diene terpolymers, styrene-ethylene-butadiene-ethylene copolymers, styrene-isoprene-styrene block copolymers or their hydrides; soft resin polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymers, propylene-α-olefin copolymers; fluorine polymers such as polyvinylidene fluoride, polytetrafluoroethylene, fluorinated polyvinylidene fluoride, polytetrafluoroethylene-ethylene copolymers; polymer compositions having ion conductivity of alkali metal ions, etc. The above positive electrode binders may be used alone or in any combination.

[0066] There is no limitation on the type of solvent used to form the positive electrode slurry, as long as it is a solvent that can dissolve or disperse the positive electrode active material, the conductive material, the positive electrode binder, and the thickener used as needed. Examples of solvents used to form the positive electrode slurry may include any of aqueous solvents and organic solvents. Examples of aqueous media may include, but are not limited to, a mixed medium of alcohol and water or water, etc. Examples of organic media may include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran; amides such as N-methylpyrrolidone, dimethylformamide, and dimethylacetamide; aprotic polar solvents such as hexamethylphosphoramide and dimethyl sulfoxide, etc.

[0067] Thickeners are generally used to adjust the viscosity of the slurry. In the case of using an aqueous medium, the thickener and styrene-butadiene rubber emulsion can be used for slurrying. The type of thickener is not particularly limited, and examples thereof may include, but are not limited to, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof. The above thickeners may be used alone or in any combination.

[0068] The type of positive electrode current collector is not particularly limited, and it can be any material known to be suitable for use as a positive electrode current collector. Examples of positive electrode current collectors may include, but are not limited to, metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and materials such as carbon cloth and carbon paper. In some embodiments, the positive electrode current collector is a metal material. In some embodiments, the positive electrode current collector is aluminum.

[0069] In order to reduce the electronic contact resistance between the positive electrode current collector and the positive electrode material layer, the surface of the positive electrode current collector may include a conductive additive or a conductive coating. Examples of conductive additives may include, but are not limited to, carbon and precious metals such as gold, platinum, and silver. Examples of conductive coatings may include a mixture layer containing an inorganic oxide, a conductive agent, and a binder.

[0070] negative electrode

[0071] The negative electrode comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode material layer comprises a negative electrode active material. In some embodiments, the chargeable capacity of the negative electrode active material is greater than the discharge capacity of the positive electrode active material to prevent lithium metal from being accidentally precipitated on the negative electrode during charging.

[0072] In some embodiments, the negative electrode active material may include natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), silicon, silicon-carbon composites, SiO w (0.5<w<1.6), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structure lithium titanate Li4Ti5O 12 , Li-Al alloy or metallic lithium, etc. Optionally, the negative electrode active material may further include an amorphous carbon material, and the amorphous carbon may be soft carbon (low temperature calcined carbon), hard carbon, mesophase pitch carbide or calcined coke, etc.

[0073] The negative electrode material layer of the present application also includes a negative electrode binder. The negative electrode binder can improve the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector. The type of negative electrode binder is not particularly limited, as long as it is a material that is stable to the non-aqueous electrolyte or the solvent used in the manufacture of the electrode. In some embodiments, the negative electrode binder includes a resin binder. Examples of resin binders include, but are not limited to, fluororesins, polyacrylonitrile (PAN), polyimide resins, acrylic resins, polyolefin resins, and the like. When an aqueous solvent is used to prepare the negative electrode mixture slurry, the negative electrode binder includes, but is not limited to, carboxymethyl cellulose (CMC) or its salt, styrene-butadiene rubber (SBR), polyacrylic acid (PAA) or its salt, polyvinyl alcohol, and the like.

[0074] The negative electrode material layer of the present application also includes a conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent, as long as the purpose of the present application can be achieved. For example, the negative electrode conductive agent can be at least one of acetylene black, Ketjen black, carbon nanotubes, carbon fibers, carbon dots or graphene, and the above-mentioned carbon nanotubes can include but are not limited to at least one of single-walled carbon nanotubes or multi-walled carbon nanotubes.

[0075] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the negative electrode current collector may include copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a polymer substrate covered with a conductive metal, etc. Among them, the conductive metal includes but is not limited to copper, nickel or titanium, and the material of the polymer substrate includes but is not limited to at least one of polyethylene, polypropylene, ethylene propylene copolymer, polyethylene terephthalate, polyethylene naphthalate or poly(p-phenylene terephthalamide). In the present application, there is no particular restriction on the thickness of the negative electrode current collector and the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4μm to 12μm, and the thickness of the single-sided negative electrode material layer is 30μm to 160μm. In the present application, the negative electrode mixture layer can be arranged on one surface in the thickness direction of the negative electrode current collector, or on two surfaces in the thickness direction of the negative electrode current collector. It should be noted that the "surface" here can be the entire area of ​​the negative electrode current collector or a partial area of ​​the negative electrode current collector. This application has no special restrictions as long as the purpose of this application can be achieved.

[0076] The present application has no particular restrictions on the compaction density of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the compaction density of the negative electrode sheet can be 1.0 g / cm 3 Up to 1.85g / cm 3 The present application has no particular limitation on the cold pressing pressure of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the cold pressing pressure of the negative electrode sheet can be 3 tons to 30 tons.

[0077] Optionally, the negative electrode plate may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, which may be at least one of the above conductive agent and the above binder. The present application has no particular restrictions on the mass ratio of the conductive agent and the binder in the conductive layer, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the thickness of the conductive layer, as long as the purpose of the present application can be achieved, for example, the thickness of the conductive layer is 1μm to 10μm.

[0078] Diaphragm

[0079] In the present application, a diaphragm is usually provided between the positive electrode and the negative electrode. The diaphragm is used to separate the positive electrode plate and the negative electrode plate to prevent internal short circuit of the electrochemical device, allow electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process.

[0080] The present application has no particular restrictions on the separator, as long as the purpose of the present application can be achieved. For example, the material of the separator may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyester (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid; the type of the separator may include at least one of woven membrane, non-woven membrane, microporous membrane, composite membrane, rolled membrane or spun membrane.

[0081] In the present application, the diaphragm may include a substrate and a surface treatment layer. The substrate may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. For example, the inorganic layer includes inorganic particles and a binder, and the present application has no particular restrictions on the above-mentioned inorganic particles, for example, it may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the above-mentioned binder, for example, it may be at least one of the aforementioned binders. The polymer layer contains a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly(vinylidene fluoride-hexafluoropropylene).

[0082] The pore size of the diaphragm in the present application is 0.01 μm to 1 μm, and the thickness is 5 μm to 50 μm. In some embodiments, the thickness of the diaphragm is greater than 1 μm, greater than 5 μm, or greater than 8 μm. In some embodiments, the thickness of the diaphragm is less than 50 μm, less than 40 μm, or less than 30 μm. When the thickness of the diaphragm is within the above range, insulation and mechanical strength can be ensured, and the rate characteristics and energy density of the electrochemical device can be ensured.

[0083] The outermost ring of the electrode assembly of the embodiment of the present application has a tail section, and the electrode assembly includes adhesive tape, which is bonded to the tail section, and the width of the adhesive tape is W mm, 10≤W≤25. For example, the value of the width of the adhesive tape can be 10, 13, 14, 17, 20, 22, 25 or a value in the range formed by any two of these values. Limiting the width of the tail section adhesive tape within the above range can improve the cycle life and self-discharge performance of the electrochemical device while taking into account the improvement of the high-temperature storage expansion phenomenon.

[0084] In some embodiments, the adhesive tape includes a substrate and an adhesive layer. The thickness of the substrate is T μm, 10 ≤ T ≤ 50. For example, the thickness of the substrate can be 10, 15, 17, 22, 34, 46, 50, or a value in the range formed by any two of these values. Limiting the thickness of the substrate to the above range can improve the cycle life and self-discharge performance of the electrochemical device while also improving the high-temperature storage expansion phenomenon.

[0085] The present application also provides an electronic device, which includes the electrochemical device of the present application. The electronic device includes but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor.

[0086] Example

[0087] Hereinafter, taking lithium-ion batteries as an example, examples and comparative examples are given to more specifically describe the implementation of the electrochemical device of the present application. Those skilled in the art will understand that the preparation method described in the present application is only an example, and any other suitable preparation method is within the scope of the present application. Various tests and evaluations are carried out according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0088] Example 1-1

[0089] (1) Preparation of positive electrode

[0090] The positive electrode active material LiNi 0.83 Co 0.08 Mn 0.07 Al 0.02O2, conductive carbon black, and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 95:2:3, and N-methylpyrrolidone (NMP) is added and stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 70wt%. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 9μm, and dried to obtain a positive electrode sheet with a single-sided coating of a positive electrode mixture layer, and the single-sided coating weight is 12.0mg / cm 2 Repeat the above steps on the other surface of the positive electrode current collector aluminum foil to obtain a positive electrode sheet coated with a positive electrode mixture layer on both sides; then cold press, strip, weld the pole ears, and dry to obtain a positive electrode sheet with a specification of 74mm×867mm.

[0091] (2) Preparation of non-aqueous electrolyte: In a dry argon atmosphere glove box, lithium hexafluorophosphate (LiPF6) was dissolved in a mixed solution of ethyl acetate and succinonitrile to obtain a non-aqueous electrolyte, wherein the mass proportion of LiPF6 based on the total mass of the non-aqueous electrolyte was 12.5%, and the remainder was propyl acetate.

[0092] (3) Preparation of negative electrode: artificial graphite is used as the negative electrode active material, and the negative electrode active material, styrene-butadiene rubber (SBR), polyacrylic acid (PAA), carbon nanotubes (CNT), and carboxymethyl cellulose (CMC) are mixed in a mass ratio of 95.8:2.4:0.5:0.5:0.8, and then deionized water is added as a solvent and stirred evenly to prepare a negative electrode slurry with a solid content of 45wt%. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and dried to obtain a negative electrode sheet with a single-sided coating of a negative electrode mixture layer, and the single-sided coating weight is 7.0mg / cm2. Repeat the above steps on the other surface of the negative electrode current collector copper foil to obtain a negative electrode sheet with a double-sided coating of a negative electrode mixture layer. After cold pressing, stripping, and welding of the pole ears, a negative electrode sheet with a specification of 76.6mm×875mm is obtained by drying.

[0093] (4) Preparation of diaphragm: A porous polyethylene film with a thickness of 15 μm was used as the diaphragm.

[0094] (5) Preparation of lithium-ion batteries: stack the positive electrode sheet, negative electrode sheet and separator in order, place the separator between the positive electrode sheet and the negative electrode sheet to isolate them, and wind them to obtain an electrode assembly. Then, stick adhesive tape to the outermost circle of the winding layer of the electrode assembly to fix the winding structure. The width of the adhesive tape is 10 mm, and the thickness of the adhesive tape substrate is 10 μm. Place the electrode assembly in a packaging bag, inject a non-aqueous electrolyte, and package it. After a process flow of storage, formation, degassing, trimming, and capacity testing, a lithium-ion battery is obtained.

[0095] <Test Method>

[0096] (1) Cycle life test

[0097] Place the lithium-ion battery in a 45℃ high temperature oven and let it stand for 60 minutes to allow the battery to reach a constant temperature. After the battery reaches a constant temperature, charge it to 4.25V at a constant current of 1C, then charge it to 0.05C at the 4.25V constant voltage, let it stand for 15 minutes, then discharge it to 2.8V at 1C, let it stand for 15 minutes, record the discharge capacity C1 of this step, then repeat the above charging and discharging process 1000 times, and record the discharge capacity C2 of the 1000th time.

[0098] Cycle life retention rate % = (C1-C2) / C1×100%.

[0099] (2) Self-discharge performance test

[0100] Take a lithium-ion battery, charge it to 4.25V at a constant current rate of 0.5C at 25℃, then charge it to 0.05C at a constant current and voltage under the same charging conditions, and let it stand for 15 minutes; then discharge it to 2.8V at a constant current of 0.5C, and let it stand for 15 minutes; then charge it at a constant current of 0.5C for 30 minutes, record the voltage V0 at the end of charging, then let it stand for 48 hours, and record the voltage V1 at this time.

[0101] Self-discharge coefficient = (V0-V1) / 48.

[0102] (3) High temperature storage thickness change rate test

[0103] Take a lithium-ion battery, charge it to 4.25V at a constant current of 0.5C at 25°C, then charge it to a current of less than or equal to 0.05C at the 4.25V constant voltage, then let it stand for 15 minutes, and measure the thickness h0 at this time; then place the lithium-ion battery in a high temperature box at 85°C, take it out after storage for 24 hours, and test the thickness h1 of the battery cell within 5 minutes after taking it out.

[0104] High temperature storage thickness change rate % = (h1-h0) / h0×100%.

[0105] The lithium ion batteries of the following embodiments or comparative examples differ from those of embodiment 1-1 only in that the types and mass proportions of the components in the non-aqueous electrolyte are adjusted according to Table 1. The performance test results of the lithium ion batteries of the embodiments and comparative examples are shown in Table 1 below.

[0106] Table 1

[0107]

[0108]

[0109] *In the above table, the positive electrode parameters and other component parameters of each example are shown in Table 2 Examples 1-25 below.

[0110] It can be seen from Table 1 that the lithium ion battery prepared in the embodiment of the present application has a better cycle capacity retention rate and a lower self-discharge level when the non-aqueous electrolyte includes a first substance, dimethyl carbonate, ethyl acetate, and a second substance, succinonitrile, glutaronitrile or adiponitrile, and the mass proportions of the first substance and the second substance satisfy 50≤M1≤70 and 0.01≤M2≤3 respectively.

[0111] In particular, the lithium-ion battery prepared in the embodiment of the present application, when the mass proportion of the first substance in the non-aqueous electrolyte further satisfies 55≤M1≤65, the lithium-ion battery has a better cycle capacity retention rate and a lower self-discharge level. In particular, the lithium-ion battery prepared in the embodiment of the present application, when the mass proportion of the second substance in the non-aqueous electrolyte further satisfies 0.1≤M2≤2, the lithium-ion battery has a better cycle capacity retention rate and a lower self-discharge level. In particular, the lithium-ion battery prepared in the embodiment of the present application, when the non-aqueous electrolyte further includes ethylene carbonate, and its mass proportion satisfies 5≤M3≤30, the lithium-ion battery has a better cycle capacity retention rate and a lower self-discharge level. In particular, the lithium-ion battery prepared in the embodiment of the present application, when the non-aqueous electrolyte further includes a third substance, and its mass proportion satisfies 0.001≤M4≤0.5, the lithium-ion battery has a better cycle capacity retention rate and a lower self-discharge level.

[0112] The lithium-ion batteries of the following Examples 2-1 to 2-31 differ from those of Example 1-25 only in that the types and mass proportions of the components in the non-aqueous electrolyte, the mass proportion of the nickel element in the positive electrode active material layer, and the tape width and tape substrate thickness parameters are adjusted according to Table 2.

[0113] Table 2

[0114]

[0115]

[0116] *In the above table, in Example 2-31, the mass ratio of Formula I-2 to Formula I-4 is 1:1, the mass ratio of Formula II-2 to Formula II-5 is 1:1, and the mass ratio of Formula III-4 to Formula III-6 is 1:1.

[0117] As can be seen from Table 2, the lithium-ion battery prepared in the embodiment of the present application, when the non-aqueous electrolyte further includes a compound of formula I, and its mass ratio satisfies 0.01≤a≤1, the lithium-ion battery has a better cycle capacity retention rate and a lower high-temperature storage thickness change rate. In particular, the lithium-ion battery prepared in the embodiment of the present application, when the non-aqueous electrolyte further includes a compound of formula II, and its mass ratio satisfies 0.01≤b≤0.3, the lithium-ion battery has a better cycle capacity retention rate and a lower high-temperature storage thickness change rate. In particular, the lithium-ion battery prepared in the embodiment of the present application, when the non-aqueous electrolyte further includes a compound of formula III, and its mass ratio satisfies 0.1≤c≤3, the lithium-ion battery has a better cycle capacity retention rate and a lower high-temperature storage thickness change rate. In particular, the lithium-ion battery prepared in the embodiment of the present application, when the mass ratio of nickel element in the positive electrode active material layer satisfies 30≤m≤56, the lithium-ion battery has a better cycle capacity retention rate and a lower high-temperature storage thickness change rate. In particular, the lithium-ion battery prepared in the embodiment of the present application, when the width of the adhesive tape satisfies 10≤W≤25, the lithium-ion battery has a better cycle capacity retention rate and a lower high-temperature storage thickness change rate. In particular, the lithium-ion battery prepared in the embodiment of the present application, when the thickness of the adhesive tape substrate satisfies 10≤T≤50, the lithium-ion battery has a better cycle capacity retention rate and a lower high-temperature storage thickness change rate.

[0118] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A non-aqueous electrolyte, characterized in that: The non-aqueous electrolyte includes a first substance and a second substance; The first substance includes at least one of dimethyl carbonate and ethyl acetate; based on the total mass of the non-aqueous electrolyte, the mass proportion of the first substance is M1%, 50≤M1≤70; The second substance includes at least one of succinonitrile, glutaronitrile or adiponitrile; based on the total mass of the non-aqueous electrolyte, the mass proportion of the second substance is M2%, 0.01≤M2≤3.

2. The non-aqueous electrolyte according to claim 1, characterized in that The non-aqueous electrolyte satisfies at least one of the following conditions: (1)55≤M1≤65; (2)0.1≤M2≤2。 3. The non-aqueous electrolyte according to claim 1, characterized in that The non-aqueous electrolyte includes ethylene carbonate; Based on the total mass of the non-aqueous electrolyte, the mass proportion of the ethylene carbonate is M3%, 5≤M3≤30.

4. The non-aqueous electrolyte according to any one of claims 1 to 3, characterized in that: The non-aqueous electrolyte includes a third substance, and the third substance includes at least one of lithium tetrafluoroborate, lithium bis(oxalato)borate, lithium difluorooxalatoborate, sodium tetrafluoroborate, sodium bis(oxalato)borate, sodium difluorooxalatoborate, potassium tetrafluoroborate, potassium bis(oxalato)borate, potassium difluorooxalatoborate, cesium tetrafluoroborate, cesium bis(oxalato)borate, or cesium difluorooxalatoborate; Based on the total mass of the non-aqueous electrolyte, the mass proportion of the third substance is M4%, 0.001≤M4≤0.

5.

5. The non-aqueous electrolyte according to any one of claims 1 to 3, characterized in that: The non-aqueous electrolyte comprises a compound of formula I: Among them, R 11 , R 12 , R 13 and R 14 are independently selected from a hydrogen atom, a fluorine atom, a C1 to C3 alkyl group or a fluorine-substituted C1 to C3 alkyl group, and R 11 , R 12 , R 13 or R 14 At least one of them is a fluorine atom; Based on the total mass of the non-aqueous electrolyte, the mass proportion of the compound of formula I is a%, and 0.01≤a≤1.

6. The non-aqueous electrolyte according to claim 5, characterized in that The compound of formula I comprises at least one of the following compounds:

7. The non-aqueous electrolyte according to any one of claims 1 to 3, characterized in that: The non-aqueous electrolyte comprises a compound of formula II: Among them, R 21 , R 22 , R 23 and R 24 At least one independently selected from a hydrogen atom, a fluorine atom, an unsubstituted or fluorine-substituted methyl, ethyl, n-propyl, isopropyl, vinyl or ethynyl group; Based on the total mass of the non-aqueous electrolyte, the mass proportion of the compound of formula II is b%, and 0.01≤b≤0.

3.

8. The non-aqueous electrolyte according to claim 7, characterized in that The compound of formula II includes at least one of the following compounds:

9. The non-aqueous electrolyte according to any one of claims 1 to 3, characterized in that: The non-aqueous electrolyte comprises a compound of formula III: Among them, R 31 , R 32 , R 33 , R 34 , R 35 and R 36 independently selected from a hydrogen atom, a fluorine atom, a C1 to C3 alkyl group or a fluorine-substituted C1 to C3 alkyl group; Based on the total mass of the non-aqueous electrolyte, the mass proportion of the compound of formula III is c%, and 0.1≤c≤3.

10. The non-aqueous electrolyte according to claim 9, characterized in that The compound of formula III includes at least one of the following compounds:

11. An electrochemical device, characterized in that: comprising an electrode assembly and the non-aqueous electrolyte according to any one of claims 1 to 10; The electrode assembly comprises a positive electrode, a separator and a negative electrode which are sequentially stacked and wound; the positive electrode comprises a positive electrode current collector and a positive electrode active material layer arranged on at least one surface of the positive electrode current collector, and the positive electrode active material layer comprises nickel element; Based on the total mass of the positive electrode active material layer, the mass proportion of the nickel element is m%, and 30≤m≤56.

12. The electrochemical device according to claim 11, characterized in that The outermost circle of the electrode assembly has a tail section; the electrode assembly includes adhesive tape, and the adhesive tape is bonded to the tail section; the width of the adhesive tape is W mm, 10≤W≤25.

13. The electrochemical device according to claim 12, characterized in that The adhesive tape comprises a substrate and an adhesive layer; the thickness of the substrate is T μm, 10≤T≤50.

14. An electronic device, characterized in that: An electrochemical device comprising any one of claims 11 to 13.